PATHOGENESIS, DIAGNOSTICS AND IMMUNOTHERAPY OF IMMUNOPATHOLOGICAL STATES. IMMUNOLOGY OF INFECTIONS - Editorial article (Медицинская иммунология, 2014)
Патогенез, диагностика и иммунотерапия иммунопатологических состо яний. Иммунология инфекций.